Competitivenes and Readines of SMALB Graduate for Entering World of Work and Further Study to 4.0 Based Higher Education - Subagya Subagya; Munawir Yusuf; Erma Kumalasari; Ravik Karsidi; Priyono Priyono; Arsy Anggrellanggi (Department of Special Education, 2020)
This research aim to evaluate the competitiveness of Special High School (SMALB) graduates to enter the world of work and further study to higher education. SMALB curriculum consist of 70% vocational and 26 lesson hours and every student is given flexibility to choose two vocations. For SMALB graduates who are not ready to achieve industrial readiness, labor readiness, cultural access, job creation, it will be challenging. Tracer study used as evaluation technique for readiness of SLMAB to further study and enter the world of work. Researchers traced alumni especially in term of job search and further study and the use of competency gains at SMALB. The methodology design that used for the implementation of tracer study consist of four stages, preparation stages, implementation stages, and analytical stages lastly evaluation stages. The subject of this research were teachers and students of SMALB around Central Java Province. Accidental sampling used as sampling technique, which is a sampling technique based on google form which is distributed to all SMALB in Central Java. This was caused by the Covid-19 pandemic, resulting all the data acquired through anyone who accidentally or willing by its consent to responds the questionnaire sent to them. The research results shows that respondents have competitiveness, Alumni of SMALB have a high opportunity to enter higher education and enter the world of work, however it is not in line with the data filled by teacher that the majority (46%), alumni do not work and live at home.